Eco‐friendly ultrasonic‐assisted appraisal of herbal‐based yellow natural colorant for silk dyeing - Noman Habib; Shahid Adeel; Muhammad Ibrahim; Fazal‐ur Rehman; Muhammad Naveed; Aamir Ali; Rony Mia; Rym Mansour (Energy Science & Engineering)
Abstract The global recognition of eco‐friendly products like plant‐based dyes is escalating, driven by their exceptional biological and Ayurvedic attributes. This study isolates colorants from mango turmeric (Curcuma aromatica) using ultrasonic irradiation, supplemented with bio‐mordants to enhance color retention. Through the utilization of Response Surface Methodology and Central Composite Design, a technique that was optimized was completed to maximize coloring variables using statistical analysis. Results from 32 experimental runs reveal that optimal color depth (K/S = 19.399) was achieved with ultrasonic‐treated silk fabric (20 min exposure) using 65 mL of irradiated aqueous extract (20 min) with a pH of 5, supplemented with 1.5 g/100 mL salt of sodium chloride, maintained the temperature 75°C for the 45 min. Precoloring treatment with acacia, pomegranate, and pistachio extracts at specified concentrations enhanced colorfastness. Postdyeing, alterations in the concentrations of these extracts led to further improvements in colorfastness. Notably, adding Al+3 and Fe+2 salts, alongside tannic acid, exhibited notable effects in both pre‐ and postdyeing stages. While the colorfastness properties of unmordated silk fabric was lower than mordanted dyed silk fabric. Irradiation with ultrasonic waves significantly boosted the amount of dye that could be extracted from rhizomes of mango turmeric. Moreover, the application of bio and synthetic mordants in a strategic manner led to colorfastness ratings on silk fabric that ranged from excellent to satisfactory. This research underscores ultrasonic technologies and bio‐mordants' efficacy in sustainable dyeing processes, offering insights for developing eco‐friendly textile coloration methods.